2008
DOI: 10.1055/s-2008-1038361
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Anterior Diaphragmatic Hernia in Childhood

Abstract: Congenital anterior diaphragmatic hernias (ADH) account for 2 - 6 % of diaphragmatic defects, whereas acquired ADH are rare. These hernias are most often the result of blunt or penetrating trauma. This is the first report of iatrogenic ADH in childhood. Two children with asymptomatic, iatrogenic ADH were diagnosed at 6 and 12 months of age, respectively. Both had undergone previous cardiac surgery requiring pericardial drainage. The ADH was seen on an incidental chest X-ray in one patient, and during a laparos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…The majority of the handful of iatrogenic diaphgramatic hernias reported in the literature are in adults, with only one previously reported case report in the pediatric population [2]. Bettolli et al [2] reported two cases of incarcerated bowel following peri-cardial drain placements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the handful of iatrogenic diaphgramatic hernias reported in the literature are in adults, with only one previously reported case report in the pediatric population [2]. Bettolli et al [2] reported two cases of incarcerated bowel following peri-cardial drain placements.…”
Section: Discussionmentioning
confidence: 99%
“…Bettolli et al [2] reported two cases of incarcerated bowel following peri-cardial drain placements. Here we report a case of iatrogenic diaphragmatic hernia resulting in strangulated bowel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very rarely acquired ADH can be iatrogenic. There are only three cases of acquired ADH reported in the pediatric age group (Bettolli et al, 2008;Dutta and Albanese, 2007). All the three cases were seen following cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired anterior diaphragmatic hernias on the other hand are very rare and usually seen following blunt or penetrating trauma. Iatrogenic anterior diaphragmatic hernia is extremely rare and only three cases were reported in children (Bettolli et al, 2008;Dutta and Albanese, 2007). This report describes the fourth iatrogenic anterior diaphragmatic hernia in a child that was repaired laparoscopically.…”
Section: Introductionmentioning
confidence: 88%